The EU Cohesion Policy Financing for the Period 2007–2013 - Boneva, Svetla (Research Papers, 2009)
The endeavour of the European Union (EU) to reduce economic and social disparities between EU regions formulate the EU cohesion policy. The cohesion policy is practically implemented by commitments of public finance transfers coming from the EU budget to the member states, managed by defined rules and procedures. This policy, financed by the EU budget, has been co-financed by other public and private financial resources. The purpose of the EU cohesion policy is on one hand to re-distribute financial resources from richer to poorer regions and social groups as well as to create new resources investing in regions and people.